2017
DOI: 10.12788/jhm.2685
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Geriatric Syndromes with Hospital Outcomes

Abstract: BACKGROUND: Frailty, history of dementia (HoD), and acute confusional states (ACS) are common in older patients admitted to hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…Eleven studies had a small sample size (range: 42‐395), were conducted in a single hospital (‐ward), or showed a sex distribution not representative of the PWD population . Thirty‐three studies met the criteria for comparability based on design or analysis, thereof 8 studies controlled or matched for 1 factor and 25 studies for at least 2 factors . Fourteen studies reported multivariate and descriptive results for LOS, and 5 studies solely multivariate results .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies had a small sample size (range: 42‐395), were conducted in a single hospital (‐ward), or showed a sex distribution not representative of the PWD population . Thirty‐three studies met the criteria for comparability based on design or analysis, thereof 8 studies controlled or matched for 1 factor and 25 studies for at least 2 factors . Fourteen studies reported multivariate and descriptive results for LOS, and 5 studies solely multivariate results .…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐three studies met the criteria for comparability based on design or analysis, thereof 8 studies controlled or matched for 1 factor and 25 studies for at least 2 factors . Fourteen studies reported multivariate and descriptive results for LOS, and 5 studies solely multivariate results . Thirteen studies did not report any information on significance level …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of institutionalisation in our cohort was 16.8%, which is relatively high in comparison to the overall (hospital-wide) institutionalisation rate in patients over 74 years old (9.9%). 13 This may refl ect the high clinical complexity of older PD patients requiring admission to our hospital. This is also consistent with previous observations that the progressive nature of PD often results in patients seeking long term care sooner than non-PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 Measures All measures were collected during routine clinical care. All DME wards routinely practice Comprehensive Geriatric Assessment (CGA).…”
Section: Study Design and Settingmentioning
confidence: 99%